Production of bioethanol from tapioca starch using Saccharomyces cerevisiae : effects of temperature and agitation speed - Muhammad Fauzi, Ibrahim (2009)
Production of bioethanol from tapioca starch involves two processes which are enzymatic hydrolysis and fermentation. The objective of the present study was to investigate the influences of temperature and agitation speed on the production of bioethanol from tapioca starch using Saccharomyces cerevisiae. The fermentation was conducted under various temperatures (30, 35 and 37°C) and agitation speeds (100, 200 and 300 rpm) in 250 mL shake flask. The cell density, glucose consumption and ethanol concentration were analyzed. The ethanol concentration in the fermentation broth increased rapidly with the increased of temperature and agitation speed. The high temperature resulted in the higher cell density and higher glucose consumption. The high agitation speeds also preferred for both cell density and glucose consumption. The maximum ethanol concentration of 57.8 mg/L was obtained at a temperature of 35°C and 200 rpm of agitation speed